Tympanometry Assessment of 61 Inbred Strains of Mice - Zheng, Qing Yin (2007)
Otitis Media (OM) accounts for more than 20 million clinic visits in the United States every year. Resistance to antibiotics has hampered current management of the disease. Identification of genetic factors underlying susceptibility to OM is greatly needed in order to develop alternative treatment strategies. Genetically defined inbred mouse strains offer a powerful tool for dissecting genetic and environmental factors that may lead to OM in mice. Here we report a study of middle ear function of 61 genetically diverse inbred strains of mice using tympanometry. Of the 61 inbred strains tested, the 129P1/ReJ, 129P3/J, 129S1/SvImJ, 129X1/SvJ, A/HeJ, BALB/cJ, BUB/BnJ, C57L/J, EL/SuzSeyFrkJ, FVB/NJ, I/LnJ, LP/J, NZB/BlNJ, PL/J and YBR/Ei strains exhibited tympanograms that were statistically different from other healthy strains according to parameters including middle ear pressure, volume and compliance. These differences are most likely the result of genetic factors that, when understood, will facilitate prevention and treatment of otitis media in humans. In addition, a negative correlation between age and compliance of the tympanic membrane was discovered. This is the first report to successfully use tympanometry to measure mouse middle ear function, which has been a challenge for the hearing research field because of the mouse’s tiny ear size.